Smartphone Use and Mental Health: The Explanatory Role of Fear of Missing Out Among Information Systems Students - Nasrah Nasrah; Muhammad Rachmat; Muhammad Arsyad Rahman; Kezia Batara Patilangi; Nur Resky (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Mental health challenges among university students have become increasingly associated with the growing presence of digital technology, especially smartphones. This study explores how smartphone use and the psychological phenomenon of Fear Of Missing Out (FoMO) relate to mental health among Information Systems students at Hasanuddin University, within the broader context of modern campus life. However, evidence integrating smartphone use patterns, FoMO, and mental health among Indonesian university students remains limited. Methods: Using a cross-sectional quantitative design, data were collected from 222 purposively selected participants. Smartphone use was categorized by intensity and activity type, FoMO was measured using the Fear of Missing Out Scale (FoMOs); and mental health was assessed with the Depression Anxiety Stress Scale-21 (DASS-21). Data were analyzed using Chi-Square tests (? = 0.05) to determine significant associations across variables. Results: The findings revealed that students with high-intensity smartphone use were significantly more likely to experience severe stress (30.4%), moderate depression (32.6%), and severe anxiety (42.4%) (p < 0.001.). Likewise, those who primarily used smartphones for social connection reported greater levels of severe stress (40.5%) and depression (22.8%) compared to students who used them mainly for information or entertainment (p < 0.001.). High FoMO levels were also strongly associated with poorer mental health outcomes, including severe stress (35.0%) and very severe anxiety (43.3%) (p < 0.001.). Conclusion:Overall, these results suggest that not only the duration of smartphone use but also its purpose and related psychological factors are associated with students’ mental well-being. The findings underscore the potential value of campus-based interventions focusing on digital literacy, mental health awareness, healthier coping strategies, and evidence-informed approaches to addressing FoMO among university students. In particular, FoMO emerged as an important correlate of mental health outcomes, supporting the need for interventions that promote responsible digital engagement and FoMO-aware coping strategies to support student well-being.